PENGARUH EFEKTIVITAS TATA KELOLA PERUSAHAAN TERHADAP PENCEGAHAN KECURANGAN DALAM PELAPORAN KEUANGAN - Rheinilda Febri Lyandani; Agus Purwanto (Diponegoro Journal of Accounting, 2025)
This study aims to test and analyze the influence of corporate governance effectiveness focusing on the characteristics of the board of commissioners and audit committees on the prevention of fraudulent financial reporting as measured using Beneish M-Score. This type of research is a quantitative research using secondary data from the annual reports and audited financial statements of manufacturing companies listed on the Indonesia Stock Exchange for 2021-2023. The research sample was taken using the pusposive sampling technique with a total of 216 samples. Multiple linear regression analysis was used to test the hypotheses. The results of this study show that the characteristics of the board of commissioners, which include the independence of the board of commissioners, the existence of female members of the board of commissioners, the financial expertise of the board of commissioners, and the frequency of board of commissioners meetings as well as the characteristics of the audit committee which include the financial expertise of the audit committee and the frequency of audit committee meetings are proven to be able to prevent fraudulent financial reporting.